Afrontamiento psicológico de los procedimientos médicos invasivos y dolorosos aplicados para el tratamiento del cáncer infantil y adolescente: la perspectiva cognitivo-conductual - Méndez, Francisco Xavier; Ortigosa, Juan Manuel; Riquelme, Antonio (Psicooncología, 2009)
Psychological coping with childhood cancer involves the use of strategies and resources that help children and their families undergo the disease with the fewest possible emotional and behavioural problems. In the field of Psychology, techniques and programs have been developed and adapted with the aim of minimising the psychological impact of the diagnosis and treatment of childhood and adolescent cancer. The present paper reviews psychological procedures based on the cognitive- behavioural paradigm, such as transmission of information, coping skills training, the use of audiovisual materials, games, bibliotherapy, and humour. It considers the use of such procedures in children and adolescents and the role of parents in the preparation.